Surgical Management of Cleft Lip and Palate: A Multi-Center Survey of Causes, Complications, and Variations in Kerbala - Sarmad Jaafar Mohammed Alrubaye (Academia Open, 2025)
Background: Cleft lip and palate represent common congenital anomalies with substantial regional variation in presentation and management outcomes. Specific Background: In Kerbala, Iraq, comprehensive data on cleft phenotype distribution, surgical practices, and postoperative complications remain limited despite the condition's prevalence of approximately 1 per 1000 live births. Knowledge Gap: Existing literature lacks detailed regional profiles characterizing phenotype patterns, perioperative protocols, and complication rates specific to this population. Aims: This retrospective chart review examined 55 patients across three Kerbala hospitals to document cleft phenotype distribution, laterality, surgical management approaches, and postoperative outcomes. Results: Cleft lip and palate constituted the predominant phenotype (69.1%), with male predominance (54.55%) and unilateral presentation (67.3%) most common. Primary repairs utilized absorbable sutures with brief hospitalization (81.81% discharged within 1-2 days). Alveolar bone grafting occurred in 34.7% of cases. Postoperative complications included fistula formation (12.7%), scarring (27.2%), and dehiscence (18%), requiring revision surgery in 12.7% of patients. Novelty: This study provides the first comprehensive regional profile of cleft management in Kerbala, establishing baseline metrics for phenotype distribution and surgical outcomes. Implications: Findings highlight the necessity for standardized outcome tracking, enhanced multidisciplinary care protocols, and targeted interventions addressing persistent complications to optimize functional and aesthetic results in this population.Highlight : Cleft lip and palate predominated (69.1%) with unilateral clefts more common and male predominance observed. Primary repair used absorbable sutures with 1-2 day hospital stays; bone grafting performed in 34.7% of cases at ages 7-12 years. Main complications were fistula formation (12.7%) and scarring (27.2%), requiring multidisciplinary follow-up for optimal outcomes Keywords : left Lip and Palate, Surgical Management, Postoperative Complications, Phenotype Distribution, Alveolar Bone Grafting